Soluble CD83 ameliorates experimental colitis in mice - Eckhardt, Jenny; Kreiser, Simon; Döbbeler, Marina; Nicolette, C.; Debenedette, M. A.; Tcherepanova, I. Y.; Ostalecki, Christian; Pommer, A. J.; Becker, Christoph; Günther, Claudia; Zinser, E.; Mak, T. W.; et al. (Mucosal Immunology, 2014)
The physiological balance between pro- and anti-inflammatory processes is dysregulated in inflammatory bowel diseases (IBD) as in Crohn's disease and ulcerative colitis. Conventional therapy uses anti-inflammatory and immunosuppressive corticosteroids to treat acute-phase symptoms. However, low remission rate and strong side effects of these therapies are not satisfying. Thus, there is a high medical need for new therapeutic strategies. Soluble CD83, the extracellular domain of the transmembrane CD83 molecule, has been reported to have interesting therapeutic and immunosuppressive properties by suppressing dendritic cell (DC)-mediated T-cell activation and inducing tolerogenic DCs. However, the expression and function of CD83 in IBD is still unknown. Here, we show that CD83 expression is upregulated by different leukocyte populations in a chemical-induced murine colitis model. Furthermore, in this study the potential of sCD83 to modulate colitis using an experimental murine colitis model was investigated. Strikingly, sCD83 ameliorated the clinical disease symptoms, drastically reduced mortality, and strongly decreased inflammatory cytokine expression in mesenteric lymph nodes and colon. The infiltration of macrophages and granulocytes into colonic tissues was vigorously inhibited. Mechanistically, we could show that sCD83-induced expression of indolamine 2,3-dioxygenase is essential for its protective effects.
EVALuna2:1840